Evolutionary morphology of spinal nodes of poikilotherm vertebrate animals - L. P. Goralskyi; I. M. Sokulskyi; N. L. Kolesnik; O. F. Dunaievska; N. L. Radzykhovskyi; B. V. Gutyj; S. Y. Shevchuk (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки, 2023)
An important issue of modern neuromorphology of animals is the study of spinal cord nodes, which play an important role as primary centers on the way to transmit sensory information from receptors to the central nervous system, providing appropriate reactions to the action of certain factors. The scientific article uses material that is a fragment of the research work of the department of normal and pathological morphology, hygiene and expertise “Development, morphology and histochemistry of animal organs in normal and pathological conditions”, state registration number – 0120U100796. Using anatomical, morphological, neurohistological and statistical methods of research, the histomorphology of spinal cord nodes in a comparative anatomical series of vertebrates: bony fish, amphibians, reptiles, which differ in motor activity and their place of existence in a certain environment, was clarified in the work. It has been established that in the process of phylogenesis, a certain structural and morphofunctional reorganization of the spinal nodes occurs. They differ in shape and size. Adaptation to various living conditions of animals was formed on the basis of changes in the density and size of neurons, their morphological structures, an increase in the total number of gliocytes and glial cells, and polymorphism in the degree of chromatophilia. Thus, according to neurohistological studies, it has been noted that the neurons of the spinal cord nodes of cold-blooded animals (pond frog, pond lizard) are characterized by a functional degree of relative polymorphism – chromatophilia. With the total impregnation of the spinal cord nodes with silver nitrate according to the Bolshovsky-Gross method, different intensity of staining of nerve cells is found in all the studied animals: light, light-dark and dark. It was found that the neurocytes of all groups of vertebrates differ in the volume of the perikaryon, the nucleus and the nuclear-cytoplasmic ratio, which is related to the peculiarities of species and age-related neuromorphology, the morpho-functional state of the nervous system and the type of higher nervous activity. Nissl staining of histopreparations of spinal nodes of poikilothermic animals showed that the neuroplasm of nerve cells of spinal nodes contains deep basophilic substances in the form of small grains of varying density. In carp neurons, the basophilic substance is concentrated on the periphery of the dust-like neuroplasm. Nuclear chromatin is more pronounced in the pond frog than in the carp, the depths of which are much larger. It should be noted that the highest degree of development of the protein-synthesizing apparatus is characteristic of the neurocytes of the spinal nodes of the swift lizard, compared to the previously studied vertebrates. The obtained research results have not only important general biological significance, which complements and expands modern scientific ideas about certain regularities of morpho-functional rearrangements of spinal cord nodes in a comparative anatomical series, but also serve to develop new material and substantiate the morpho-functional assessment of species morphological differences of the nervous system of poikilothermic vertebrates, adapted to different conditions of existence in the environment.